A scene from on the set with Silvana Mangano holding Guiseppe De Santi's hand, and Pedro Amendariz standing. - De Santis, Giuseppe, 1917-1997 (Z. Smith Reynolds Library, Wake Forest University, 1956)
The film takes place in a small, isolated town, Vischio, in the Apennine Mountains. The film opens to a snow-covered village as a new family arrives in the village.
Keywords: Montand, Yves, 1921-1991; Wolf hunting -- Italy -- Drama; Stills (motion pictures); Motion pictures -- Italy -- History -- Sources; Motion picture actors and actresses -- Italy; Mangano, Silvana, 1930-1989; Cefaro, Irene, 1935-; Armendariz, Pedro, 1912-1963; Apennines (Italy) -- Rural conditions -- Drama; Motion picture producers and directors -- Italy